Educational innovation in multi-classes: An exploratory survey in the small schools of the mountain communities of the Alto Caserta - Capobianco, Rosaria (Formazione & insegnamento, 2020)
This paper analyzes the teaching practices used in the multi-classes present in the “small schools” of Alto Casertano and on the importance that these are incorporated in the training of teachers as a driving force for the quality of teaching. It is necessary to deepen the training of teachers who every year, more and more often, are catapulted into multi-classes, as teaching in heterogeneous classes requires didactic skills, innovative strategies and specific competences to be able to guarantee all students real meaningful learning, in respect for cognitive development. From the analysis of the contents of the interviews with the teachers of multi-classes conducted in the primary schools of the Alto Casertano it is clear that the Problem-Based Learning (PBL), peer education and collaborative learning (Johnson & Johnson, 1994) are fundamental within the small schools, but above all how important teamwork is, that is to give life to communities of practices, for sharing good practices.